Patient's Chatting Mechanism Serious Game for Internal Medicine Practice - Lee Sim, Siew (2013)
This subject deals with an invention towards developing a Artificial Intelligent chatbot for a online serious game in the domain of medical and treatment. It lead to a creation of artificial intelligence chat-box which can communicate with user in human natural language. This robot is formulated to behave as a human patient. The artificial intelligent chatbot, Ill.Bot is being designed as a web-based language processor to analyze our human natural language by using fuzzy logic methods through web scripting. The trick of artificial intelligence is to locate the user input from the existing history or memory and match the response to related input through the use of search and match mechanism. Alongside the development of chatbot, an approaches, One-Match and All-Match Categories - algorithms and techniques had been used to enhance the process of keywords/pattern matching for chatbot.